Quidditch through the ages - Rowling, J. K. (New York : Arthur A. Levine Books, 2001)
A copy of a book from the library at Hogwart's, the school where Harry Potter and other young wizards receive their training, providing information about history and conduct of Quidditch, a sport played by competing teams on flying brooms. Proceeds from this book will go to Comic Relief U.K.
"Comic Relief"--Cover p. [4].
"Property of Hogwarts Library"--Cover.
"WhizzHard Books, 129b Diagon Alley, London.".
Written by J.K. Rowling as a fictitious author.
Book Report.
Kliatt.
Keywords: Fantasy; Games -- Fiction; Potter, Harry (Fictitious character) -- Fiction; Quidditch -- History -- Fiction; Sports -- Fiction; Games -- Fiction; Potter, Harry (Fictional character) -- Fiction; Quidditch -- History -- Fiction; Sports -- Fiction; Fantastic fiction